An improvement of photocatalytic activity of TiO2 Degussa P25 powder - Bessergenev, V. (2018)
The photocatalytic activities of Degussa P25 powders annealed at various temperatures in vacuum and air were studied together with investigations of their compositions by XPS, of their crystal structures by XRD and of their specific surface areas by BET. It is shown that the photocatalytic activity of P25 powders was remarkably enhanced after vacuum annealing; the kinetic coefficient can be raised by 75% during annealing at 400 degrees C. It is obvious that this enhancement is not related to the adhesion ability of the P25 powders. (C) 2015 Elsevier B.V. All rights reserved.